The role of cardiovascular magnetic resonance in the screening before the return-to-play of elite athletes after COVID-19: utility o futility? - Filomena, D.; Birtolo, L. I.; Penza, M.; Gualdi, G.; Maestrini, V. (The Journal of Sports Medicine and Physical Fitness, 2021)
Recent reports based on cardiovascular magnetic resonance (CMR) showed a wide range of prevalence of inflammatory heart diseases in COVID-19 convalescent athletes ranging from 0.4 up to 15%. These observations had an important impact in the field of sport cardiology opening an intense debate around the best possible screening strategy before the return-to-play. The diagnostic yield of CMR for detecting acute inflammatory disease is undebatable. However, the opportunity to use it in the screening protocol after COVID-19 has been questioned. Current evidence does not seem to support the routine use of CMR and the prescription of CMR should be based upon clinical indication.